(untitled) (Qualitative Research Journal for Social Studies, 2026)
In this paper, the author looks at Pakistan’s growing state surveillance system through the means of the internet, from a conflict perspective, drawing on panopticism theory, along with the perspectives of Governmentalities and disciplinary power as outlined by Foucault. It looks at the issues of censorship in Pakistan, with Amnesty International’s 2025 report, “Shadows of Control: Censorship and mass surveillance” in Pakistan providing a key case study. The violation of documented rights and technologies for mass surveillance and censorship of Pakistan are discussed. We find that the attention of the academic, legal and human rights literature has been focused on Pakistan in a wider context of “digital authoritarianism”. We contend that the theory of conflict with its focus on the power imbalance and domination best explains how surveillance in Pakistan further extends the interests of the power class and curbs dissent. In this point of view, we are taking a particular approach with the adoption of a panoptical effect and governmentality: The Foucaultian concept of the panoptical effect and governmentalization of power facilitates the understanding of how the citizens of Pakistan are made manageable through surveillance. The analysis highlights the state of law and policies in Pakistan and how it reflects Foucauldian process of control, which becomes a routinized and invisible machinery of control. Multiple human rights sources confirm this connection between this monitoring system and the violations of the rights to privacy, freedom of expression, freedom of association and freedom of fair trial. The paper ends by situating the surveillance regime in Pakistan within the wider ‘surveillance industry’, positioning the trade in surveillance technology as the responsibility of multinationals alongside states to ensure proper accountability, in the process, highlighting that the industry has been instrumental in rights abuses. More than thirty scholarly, legal sources support the findings.